A Study of Digital Literacy Knowledge and Understanding Among Personnel within the Communications Department, Ministry of Public Security - KEOPHASOUK, Phaythoon; Louangvilay, Xaythavy (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
Digital technology is evolving rapidly, and the transformation toward organizations that utilize digital systems to support operational processes has become both a goal and a challenge for the Government of the Lao PDR. In alignment with this national policy, the Communications Department of the Ministry of Public Security has adopted a direction that emphasizes digital transformation. To successfully achieve this goal, personnel within the department must be adequately prepared to use digital systems. This research aims to study the level of digital literacy among employees of the Communications Department of the Ministry of Public Security. The study focuses on three objectives: (1) to examine behavior in using digital technology, (2) to assess skills in using digital technology, and (3) to analyze awareness of risks and cyber-attacks. The research employed a qualitative approach using questionnaires as the data collection instrument. The sample group consisted of 212 employees, including 59 women, representing 27.83% of the sample. Statistical techniques, including mean (x̄) and standard deviation (SD), were used to analyze and present the data. The results regarding digital technology usage behavior revealed that Facebook is the most commonly used social media platform. Communication is primarily conducted via WhatsApp, including file transfers. Flash drives are commonly used for transferring large data files, while MS Word is the most frequently used tool for document management. Google Drive is the preferred cloud storage platform. Employees regularly use computers for more than 30 minutes per session and frequently utilize artificial intelligence tools in their work.